Preserving Meaning Across Dialects: Translation Strategies of Hadhrami Expressions by Yemeni Undergraduate Students - Mohammed Ahmed Al-Amri, Malak; Saaleh Ahmed Al-Haidari, Ali; Mohammed Ahmed Al-Amri, Malikah (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study explores how Yemeni undergraduate students translate Hadhrami dialectal expressions into English and examines the extent to which their translations preserve the original cultural meaning. A qualitative descriptive design supported by quantitative analysis was employed to identify students’ translation strategies and the challenges they encountered. Forty-four translation students from several Yemeni universities completed a validated test containing twenty Hadhrami expressions. The findings revealed that students primarily relied on literal translation and dynamic equivalence, while cultural substitution and paraphrasing were used less frequently. Many translations did not fully convey the intended cultural and figurative meanings of the source expressions. The study also found that linguistic, cultural, and strategic factors interacted to hinder accurate and contextually appropriate translation. These results highlight the importance of integrating cultural competence, dialect awareness, and strategy-based instruction in translation pedagogy to help students manage culturally bound dialectical expressions more effectively.